2018
DOI: 10.21315/aamj2018.23.1.2
|View full text |Cite
|
Sign up to set email alerts
|

THE RELATION BETWEEN TURNOVER INTENTION, HIGH PERFORMANCE WORK PRACTICES (HPWPs), AND ORGANISATIONAL COMMITMENT: A STUDY AMONG PRIVATE HOSPITAL NURSES IN MALAYSIA

Abstract: Turnover poses a serious threat in healthcare settings. The scarcity of healthcare professionals and particularly nurses is highlighted as one of the biggest obstacles to achieving health system efficiency and effectiveness. As such, healthcare administrators need to search for ways to retain qualified and competent nurses. This study provides a framework depicting how organisational commitment can mediate the relationship between three forms of high performance work practices (HPWPs) (performance appraisal, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 80 publications
(113 reference statements)
3
29
1
1
Order By: Relevance
“…Clinical nursing experience and training accumulated by these nursing staff enable them to provide superior services and perform their tasks efficiently. Hospital managers could implement relevant practices (e.g., objective performance appraisal mechanisms; competitive compensation) to increase the willingness of nursing staff to stay at a hospital (Nasurdin, Ling, & Khan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical nursing experience and training accumulated by these nursing staff enable them to provide superior services and perform their tasks efficiently. Hospital managers could implement relevant practices (e.g., objective performance appraisal mechanisms; competitive compensation) to increase the willingness of nursing staff to stay at a hospital (Nasurdin, Ling, & Khan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Rissanen (2017: 52) reported that, in order to be retained and to reduce incidents of turnover intent, employees expect compensation that is in line with their skills and work experience. Unless the total payment structure is perceived as internally fair and externally benchmarked for competitiveness, employees are likely to leave their organisations (Nasurdin, Tan andKhan 2018, Onah &Anikwe 2016). Location of workplace also has the potential to have an impact on employees' level of job satisfaction and, in turn, influence their turnover intentions (Nair, Mee & Cheik 2016).…”
Section: Organisational Determinants Influencing Turnover Intentionmentioning
confidence: 99%
“…Fyn et al (2019) and Johennesse and Chou (2017) found that pay and fringe benefits are predictors of turnover intention. Nasurdin, Tan and Khan (2018) emphasised that payment and fringe benefits should be externally benchmarked for fairness and competitiveness. Keng (2014) reported that employees would change their job for a 10% increment in salary.…”
Section: Organisational Determinants and Turnover Intentionsmentioning
confidence: 99%
“…According to Aizzat Mohd Nasurdin, et.,al (2018), employee turnover is one of the biggest obstacles in achieving the required scale of productivity. Performance appraisal, compensation and employment security can reduce turnover intention and increase organizational commitment.…”
Section: Literature Reviewmentioning
confidence: 99%